(untitled) (Kriminalističke teme, 2006)
This paper is a part of the comprehensive empirical research focusing on forms of social behavior manifested by the children in the schools and are considered as behavior at the very edge of social appropriateness- so called behavior at risk for delinquency. In the sample were included students from finishing grades of primary and first grades high schools in Sarajevo, in which by relative authorities was reported predelinquent behavior to the greater extent. By observing the students, class teachers distinguished 214 of them manifesting a noticeable degree of social inappropriate behavior. The whole sample was the subject to the numerous descriptive, inferential, discriminative and explanatory analyses, from which in this paper are excerpted the results of analysis of influence of exogenous, mediatory and endogenous variables on manifestation of those forms of behavior at risk for delinquency which could be viewed as first step of predelinquency, subsequently leading to delinquency itself.